Proceedings. Frontiers in Education. 36th Annual Conference 2006
DOI: 10.1109/fie.2006.322518
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to an Embedded Systems Curriculum

Abstract: Universities around the world have modified their computer engineering curricula to include courses and modules focusing on the design of embedded systems including reconfigurable hardware, real-time processing, embedded processors, and firmware/software systems. This paper describes a different approach to embedded systems education-the development of an embedded systems track within an existing computer science program. This approach allows for an intentionally designed balance of computer science, computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In Ref. , Hall et al described a different approach to embedded systems education—the development of an embedded systems track within an existing Computer Science program. According to the authors, their approach allowed for an intentionally designed balance of Computer Science, Computer Engineering, Mathematics, and Science Courses all deemed necessary for a comprehensive embedded systems program.…”
Section: Related Workmentioning
confidence: 99%
“…In Ref. , Hall et al described a different approach to embedded systems education—the development of an embedded systems track within an existing Computer Science program. According to the authors, their approach allowed for an intentionally designed balance of Computer Science, Computer Engineering, Mathematics, and Science Courses all deemed necessary for a comprehensive embedded systems program.…”
Section: Related Workmentioning
confidence: 99%
“…Many educators have indicated that completion of a significant and comprehensive hands-on project is a necessary component to better prepare students to keep up with the current technology and for further advanced computing study [1][2][3], [5]. The development of a hands-on application-oriented curriculum for undergraduate computer science (CS) or computer engineering (CE) education is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Concepts typically covered in an operating systems course that are applicable to embedded systems will also be addressed, including time management, solutions to address concurrency issues (race conditions [10]), and communications protocols. Since these issues would typically be handled by an operating system in the case of general purpose computers, different approaches are necessary for small embedded systems [11][12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%